LITERASI PERBANKAN SYARIAH: KONSEP DAN KESESUAIANNYA DENGAN NILAI-NILAI EKONOMI DALAM AL-QURAN - Sari, Annisyah Paradhita; Rambe, Riswan; Verawati, Irma (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
Literacy is part of the opportunities and challenges of Islamic banking in Indonesia, Islamic banking literacy needs to be carried out to various segments of society. The level of Islamic financial literacy is low, reaching only 9.14% in 2022. Financial literacy is an intrinsic factor that influences and motivates people to seek information and act based on what they know. Literacy can be used as a tool to further increase public understanding of Islamic banking in an effort to increase the market size of Islamic banks. In 2022, around 65.82 million people or nearly a quarter (24.00%) of Indonesia's population are in the age group between 16-30 years or are referred to as youth. Teenagers as part of Indonesian society become agents of change and have potential in the development of Islamic banks. This community service activity was carried out at the Jami' Ulayat Percut Sei Tuan Mosque. The participants who took part in this activity were the youth of the Jami' Ulayat Percut Sei Tuan Mosque Keywords: Literacy, Sharia Banking, Youth